Mapping resilience pathways of Indigenous youth in five circumpolar communities. (October 2014) - Allen, James; Hopper, Kim; Wexler, Lisa; Kral, Michael; Rasmus, Stacy; Nystad, Kristine
This introduction to the Special Issue Indigenous Youth Resilience in the Arctic reviews relevant resilience theory and research, with particular attention to Arctic Indigenous youth. Current perspectives on resilience, as well as the role of social determinants, and community resilience processes in understanding resilience in Indigenous circumpolar settings are reviewed. The distinctive role for qualitative inquiry in understanding these frameworks is emphasized, as is the uniquely informative lens youth narratives can offer in understanding Indigenous, cultural, and community resilience processes during times of social transition. We then describe key shared cross-site methodological elements of the Circumpolar Indigenous Pathways to Adulthood study, including sampling, research design, procedures, and analytic strategies. The site-specific papers further elaborate on methods, focusing on those elements unique to each site, and describe in considerable detail locally salient stressors and culturally patterned resilience strategies operating in each community. The concluding paper considers these across sites, exploring continuities and discontinuities, and the influence of cross-national social policies.